From Research to Practice in the Design of Cooperative Systems: Results and Open Challenges 2012
DOI: 10.1007/978-1-4471-4093-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Struggling Against Social Isolation of the Elderly—The Design of SmartTV Applications

Abstract: This chapter charts a work in progress in the frame of the European project AAL FoSIBLE. Our hypothesis is that virtual networks and online generational communities could offset the lack of relationship, prevent isolation and increase self-esteem for older people living alone at home. Following this purpose, we are then aiming at defining services by rethinking the use of well-known existing technologies and to broaden their scope to be more affordable by older people. This chapter describes related work on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This field is only emerging, as reported in [ 14 ], which queried Scopus and Web of Science for papers using keywords “Elderly & TV”, “Interactive & TV & Elderly”, “SmartHome”, “AAL & elderly & TV” and filtering only those related to older people and television, more than 75% of publications were released at or after 2010. Our results were in concordance with previous literature, such as the AAL FoSSIBLE project supporting social interactions through the development of smart TV applications to prevent isolation for older people living alone [ 36 ]. To meet the demand for these type of applications, the next generation of televisions must be prepared to offer interactive services and content to specific groups of users, according their characteristics and preferences [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…This field is only emerging, as reported in [ 14 ], which queried Scopus and Web of Science for papers using keywords “Elderly & TV”, “Interactive & TV & Elderly”, “SmartHome”, “AAL & elderly & TV” and filtering only those related to older people and television, more than 75% of publications were released at or after 2010. Our results were in concordance with previous literature, such as the AAL FoSSIBLE project supporting social interactions through the development of smart TV applications to prevent isolation for older people living alone [ 36 ]. To meet the demand for these type of applications, the next generation of televisions must be prepared to offer interactive services and content to specific groups of users, according their characteristics and preferences [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specify requirements: Santana-Mancilla, PC. 1,2 , Anido-Rifón, LE. 1 1 School of Telecommunications Engineering University of Vigo Vigo, Spain Email: psantana@uvigo.es, lanido@gist.uvigo.es Identify all the requirements and the users' objectives that are needed for success with the product.…”
Section: Methodsmentioning
confidence: 99%
“…This is a project to support social interactions through the development of smart TV applications to prevent isolation for older people living alone [2].…”
Section: Aal Fossiblementioning
confidence: 99%
“…Social support networks among older adults are significantly understudied [51,72]. However, studies on this subject have shown promising results [2,49,52,71,74].…”
Section: Related Workmentioning
confidence: 99%